Investigation of the Structural Composition of Fe-Mn-Si-Ti-Al-N-C Alloys and the Solubility of Elements in α-Iron - Filonenko, Nataliia; Babachenko, Olexander; Kononenko, Hanna; Baskevich, Alexander (East European Journal of Physics, 2021)
The study of the structural components of Fe-Mn-Si-Ti-Al-N-C with the carbon content of 0.50-0.60% (wt.), Silicon 0.80-0.90% (wt.), Manganese 0.90-0.95% ( wt. ), Aluminum - 0.20-0.30% (wt.), Titanium - 0.02-0.03% (wt.), Nitrogen - 0.015-0.02% (wt.), the rest - iron. Microstructural, micro-X-ray spectral and X-ray phase analyzes were used to determine the structural state of the alloys. It is shown that after crystallization and a number of phase transformations the structure of the alloy was presenteda - iron alloyed with cementite, oxides, nitrides and carbonitrides. Using the quasi-chemical method, the free energy dependence of the solid solution of α-iron alloyed with silicon, manganese and titanium was obtained. In α-iron, it can dissolve up to 0.016% (at.) Carbon, manganese up to 1.3% (at.), Silicon - 1.0% (at.), and titanium up to 0.5% (at.), which is consistent with experimental results.